2015
DOI: 10.1017/s1368980015002062
|View full text |Cite
|
Sign up to set email alerts
|

Red and processed meat consumption and mortality: dose–response meta-analysis of prospective cohort studies

Abstract: Objective: To examine and quantify the potential dose-response relationship between red and processed meat consumption and risk of all-cause, cardiovascular and cancer mortality. Design: We searched MEDLINE, Embase, ISI Web of Knowledge, CINHAL, Scopus, the Cochrane library and reference lists of retrieved articles up to 30 November 2014 without language restrictions. We retrieved prospective cohort studies that reported risk estimates for all-cause, cardiovascular and cancer mortality by red and/or processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
230
2
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(255 citation statements)
references
References 58 publications
11
230
2
12
Order By: Relevance
“…In high-income Western countries, large prospective studies and meta-analyses generally show that total mortality rates are modestly higher in participants who have high intakes of both red and processed meat than in those with low meat intakes, whereas no or moderate inverse associations have been observed for poultry (27)(28)(29)(30). However, part of this may be due to the association of high meat intakes with other major risk factors such as smoking, alcohol consumption, and obesity because the information needed to remove statistically the influence of these confounding factors may not be available.…”
Section: Effects On Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-income Western countries, large prospective studies and meta-analyses generally show that total mortality rates are modestly higher in participants who have high intakes of both red and processed meat than in those with low meat intakes, whereas no or moderate inverse associations have been observed for poultry (27)(28)(29)(30). However, part of this may be due to the association of high meat intakes with other major risk factors such as smoking, alcohol consumption, and obesity because the information needed to remove statistically the influence of these confounding factors may not be available.…”
Section: Effects On Healthmentioning
confidence: 99%
“…For example, a recent meta-analysis reported that high intakes of processed meat (but not unprocessed red meat) are associated with a moderate increase in the risk for mortality from cardiovascular disease (Fig. 2B) (27,30). Some studies have also suggested that high intakes of processed meat are associated with an increased risk for other chronic diseases, such as diabetes (33), and with weight gain in adults (34).…”
Section: Effects On Healthmentioning
confidence: 99%
“…CVD has been the leading cause of death in the United States since the 1950s and is currently attributable to 610,000 US deaths each year (1). Historically, epidemiologic cohort data support associations between high red meat intake and CVD-related events (2,3) and mortality (4)(5)(6). This notion is currently being challenged due to data collection methods that group red meat with processed meat and/or inconsistent nomenclature and classification of red meat throughout the literature (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…O'Sullivan og medarbeideres metaanalyse, som er nevnt i kapittel 7C, fant at et høyt inntak av rødt og bearbeidet kjøtt var forbundet med økt total dødelighet (+ 17-21 %) og bearbeiet kjøtt med økt kardiovaskulaer dødelighet (+ 17 %). Dette støttes av nyere metaanalyser 293 , men i hvilken grad det kan tilskrives fettinnhold vites ikke.…”
Section: Fett Fra Kjøttunclassified